PERTAHANAN BUDAYA DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Suvi Fitriani; Syafrial Syafrial; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research entitled Cultural Defense in the novel of the Hidden Moon in the Sky of America by Hanum Salsabiela Rais and Rangga Almahendra. The purpose of this study is to describe how the cultural defense in the novel Moon Breaded in the Sky of America by Hanum Salsabiela Rais and Rangga Almahendra. This type of research is descriptive qualitative research that tries to tell the existing problem solving based on existing data. The source of data in this study is cultural defense in the novel Moon Breaded in the Sky America by Hanum Salsabiela Rais and Rangga Almahendra. Based on the research, 84 cultural defense data were found in the form of language, knowledge system, life equipment and technology, belief or religious system. The details of data related to cultural defense are (1) language 2 data; (2) knowledge system 2 data; (3) live equipment and technology 3 data; (4) trust or religious system 47; and data that do not preserve the culture are (1) language 21 data; (2) religious system 2 data; (3) live equipment and technology 7 data; (4) belief or religious system 0 data. The results of this form of data that retain culture and do not maintain the culture in the novel Moon Splitted in the Sky America by Hanum Salsbiela Rais and Rangga Almahendra.Keywords: defense, culture, the Moon is split in the sky of America.